Evaluation of Cotton Responses to Fomesafen-Based Treatments Applied Preemergence. (3rd May 2018) - Li, Xiao; Grey, Timothy; Vencill, William; Freeman, James; Price, Katilyn; Cutts, George; Price, Andrew
Abstract: Fomesafen provides effective control of glyphosate-resistant Palmer amaranth in cotton. However, cotton seedlings can be injured when fomesafen is applied PRE. Therefore, greenhouse and field experiments were conducted at Athens, GA, and at six locations in Alabama and Georgia in 2013 and 2016 to evaluate cotton growth and yield response to fomesafen applied PRE at 70, 140, 280, 560, 1, 120, or 2, 240 g ai ha −1, and in combination with pendimethalin, diuron, acetochlor, and fluridone at 1×label rates. Greenhouse bioassays indicated that fomesafen reduced cotton height and dry weight with increasing rate in Cecil sandy loam and Tifton loamy sand but not in Greenville sandy clay loam––possibly as a result of this soil's higher organic matter (OM) and clay content. Fomesafen applied at 2, 240 g ai ha −1 reduced cotton stand by as much as 83% compared to the nontreated check (NTC) at all field locations except Alabama's Macon and Baldwin counties, and 1, 120 g ai ha −1 reduced cotton stand only at Pulaski County, GA, by 52%. Cotton height was reduced by the two highest rates of fomesafen at all locations except Clarke County, GA, and Baldwin County, AL. Injury data indicated more visual injury followed increasing fomesafen rates, and high-rate treatments produced more injury in sandier soils. Cotton yield was unaffected by herbicide treatments at any location, except for the 1, 120 g ai ha −1 rate at Pulaski County (49% yield loss compared to NTC), 2, 240 g ai ha −1 at Pulaski County (72% yield loss), and Tift County (29% yield loss). These data indicated cotton yield should not be negatively affected by fomesafen applied PRE alone within label rates or in combination with pendimethalin, diuron, acetochlor, and fluridone at 1×label rates, although some visual injury, or stand or height reduction may occur early in the growing season.